2007
DOI: 10.1007/s11325-007-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional contribution of mandibular advancement to awake upper airway patency in obstructive sleep apnea

Abstract: In the narrowed upper airway of patients with obstructive sleep apnea (OSA), a neuromuscular compensatory mechanism augments the activity of the upper airway dilator muscles in defense of upper airway patency, particularly during inspiration. We hypothesized that mechanical enlargement of the upper airway by a mandibular advancement oral appliance would permit a reduction in this neuromuscular compensation during wakefulness. To test this hypothesis, we focused on changes in the cross-sectional (CS) area of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…We also found that the cross-sectional area became significantly smaller during inspiration despite mandibular advancement, although the cross-sectional area at end-tidal expiration increased, as expected. We speculated that input from upper airway mechanoreceptors during inspiration decreased phasic GGEMG, since protrusion of the mandible reduced the propensity for upper-airway collapse [5]. Based on the results of the present study and the previous report [5], we can further hypothesise that GGEMG activity could be controlled to maintain a target level of cross-sectional area and patency of the upper airway.…”
Section: Dose-dependent Effects Of Mandibular Protrusion On Genioglossupporting
confidence: 71%
See 3 more Smart Citations
“…We also found that the cross-sectional area became significantly smaller during inspiration despite mandibular advancement, although the cross-sectional area at end-tidal expiration increased, as expected. We speculated that input from upper airway mechanoreceptors during inspiration decreased phasic GGEMG, since protrusion of the mandible reduced the propensity for upper-airway collapse [5]. Based on the results of the present study and the previous report [5], we can further hypothesise that GGEMG activity could be controlled to maintain a target level of cross-sectional area and patency of the upper airway.…”
Section: Dose-dependent Effects Of Mandibular Protrusion On Genioglossupporting
confidence: 71%
“…We speculated that input from upper airway mechanoreceptors during inspiration decreased phasic GGEMG, since protrusion of the mandible reduced the propensity for upper-airway collapse [5]. Based on the results of the present study and the previous report [5], we can further hypothesise that GGEMG activity could be controlled to maintain a target level of cross-sectional area and patency of the upper airway. We recognise that this study merely demonstrates associations, not causality.…”
Section: Dose-dependent Effects Of Mandibular Protrusion On Genioglossupporting
confidence: 71%
See 2 more Smart Citations
“…In advancing the mandible, the splints widen and stretch the muscles, which concurrently produce an increase in electromyographic activity, widening the airway and improving airflow. 1,2,14,17,19,26 Thirteen patients (86.7%) exhibited some degree of tooth sensitivity, especially on awakening in the morning. With splint use, five patients (33%) complained of excessive salivation at night and one patient (6.6%) complained of dry mouth at night.…”
Section: Discussionmentioning
confidence: 99%